Women and law : contemporary problems - Sarkar, Lotika; Sivaramayya, B., 1928-; Indian Association for Women's Studies; National Conference on Women's Studies (New Delhi : Vikas Pub. House, 1994)
Selection from the papers presented at the four National Conference on Women's Studies held in 1982, 1984, 1986, and 1988.
"Copyright: Indian Association for Women's Studies"--T.p. verso.
Includes bibliographical references.
Keywords: Women's studies -- India